2020
DOI: 10.3390/diagnostics10090716
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Cytokine and Chemokine Gene Expression for Diagnosing Latent and Active Tuberculosis

Abstract: Tuberculosis infection exhibits different forms, namely, pulmonary, extrapulmonary, and latent. Here, diagnostic markers based on the gene expression of cytokines and chemokines for differentiating between tuberculosis infection state(s) were identified. Gene expression of seven cytokines (Interferon gamma (IFN-γ), Interferon gamma-induced protein 10 (IP-10), Interleukin-2 receptor (IL-2R), C-X-C Motif Chemokine Ligand 9 (CXCL-9), Interleukin 10 (IL-10), Interleukin 4 (IL-4), and Tumor Necrosis Factor alpha (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…In vitro fertilization and embryo transfer and surrogacy have a role in selected cases. Newer molecule tests like genomics and nucleus receptors are being developed for early diagnosis of TB including FGTB [ 50 ]. Novel biotechniques, nanoparticles and stem cell transplantation are being developed for regeneration of endometrium (in Asher man’s syndrome), fallopian tubes (fallopian tubes blockage and damage) and for ovaries (damaged ovaries).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro fertilization and embryo transfer and surrogacy have a role in selected cases. Newer molecule tests like genomics and nucleus receptors are being developed for early diagnosis of TB including FGTB [ 50 ]. Novel biotechniques, nanoparticles and stem cell transplantation are being developed for regeneration of endometrium (in Asher man’s syndrome), fallopian tubes (fallopian tubes blockage and damage) and for ovaries (damaged ovaries).…”
Section: Discussionmentioning
confidence: 99%
“…Multifunctional CD4+ T lymphocytes producing multiple cytokines along with IL‐2 can protect against TB reactivation 52–54 . In addition, patients with active TB have increased levels of IL‐2R, and depict of IL‐2‐inducible T‐cell kinase, highly expressed in Th1 and Th17 cells, have been shown to induce the vulnerability of TB in murine studies 55,56 . Therefore, basiliximab might be associated with a lower risk of TB, especially compared to ATG.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2018) identified a six-cytokine biosignature (including IFNγ, IL-10, IL-1Ra, IP-10, VEGF, and IL-12p70) to discriminate between aTB and LTBI, resulting in a sensitivity of 88.2% and a specificity of 92.1% in a biomarker validation cohort (n = 216) and a sensitivity of 85.7% and a specificity of 91.3% in a prospectively recruited clinical validation cohort (n = 194), respectively. Coincidentally, Korma et al (2020) evaluated the sensitivity, specificity, and accuracy of the combination of seven cytokines (IFN-γ, IP-10, IL-2R, C-X-C Motif Chemokine Ligand 9 (CXCL-9), IL-10, IL-4, and TNF-α) based on gene expression in differentiating between aTB and LTBI. They demonstrated that the combination of IL-10, IP-10, and IL-4 could differentiate pulmonary patients with TB from latent patients with TB with a sensitivity and specificity of 77.1% and 88.1%, respectively (Korma et al, 2020).…”
Section: Cytokinesmentioning
confidence: 99%
“…Coincidentally, Korma et al (2020) evaluated the sensitivity, specificity, and accuracy of the combination of seven cytokines (IFN-γ, IP-10, IL-2R, C-X-C Motif Chemokine Ligand 9 (CXCL-9), IL-10, IL-4, and TNF-α) based on gene expression in differentiating between aTB and LTBI. They demonstrated that the combination of IL-10, IP-10, and IL-4 could differentiate pulmonary patients with TB from latent patients with TB with a sensitivity and specificity of 77.1% and 88.1%, respectively (Korma et al, 2020). Luo et al (2019) identified potential biomarkers from 38 plasma cytokines to discriminate among the different stages of M. tuberculosis infection in its study participants, who were composed of 78 patients with aTB, 73 patients with LTBI, and 76 HCs.…”
Section: Cytokinesmentioning
confidence: 99%